Penerapan Sistem Computer Assisted Test (CAT) Bagi Calon Pegawai Negeri Sipil (CPNS) Sebagai Kontribusi Untuk Mewujudkan Good Governance Dikota Pekanbaru - Geovani Meiwanda; Fitri Ani (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Good governance arises because of a bad government system, good governance is born in order to improve bad governance by implementing participatory policies. One of the efforts made to realize good governance is by implementing a participatory, transparent system. Accountability, effectiveness and efficiency. One of the ways to create a superior state civil apparatus is to implement a computer assisted test (CAT) system in the recruitment process. In this study, researchers used qualitative research methods and literature studies. With interview data collection methods and secondary data. The result of this study is that the computer assisted test (CAT) system contributes to realizing good governance in the city of Pekanbaru